(untitled) - Lougheed, Lin (Oxford, 2003)
Learning to listen: Making sense of spoken English. Learning to listen acknowledges the difficulty that many students have, understanding real spoken english and helps them to; listen appropriately, understand correctly, make sense of what they hear. Learning to listen makes the classoom experience as interesting and varied as the real world by presenting and celebrating the many different ways that people communicate with each other in english
Keywords: English language,English language; Textbooks for foreign speakers,Spoken English